2021
DOI: 10.1111/ctr.14206
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived cell‐free DNA is associated with cardiac allograft vasculopathy

Abstract: Background The role of donor‐derived cell‐free DNA (dd‐cfDNA) in screening for cardiac allograft vasculopathy (CAV) is unknown. We hypothesized that dd‐cfDNA correlates with CAV, markers of inflammation, and angiogenesis in stable heart transplant (HT) recipients. Methods Sixty‐five HT recipients ≥2 years post‐transplant, without recent rejection, were stratified by high (≥0.12%) versus low levels (<0.12%) of dd‐cfDNA. A targeted amplification, next‐generation sequencing assay (AlloSure®; CareDx, Inc.) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
1
14
0
1
Order By: Relevance
“…For dd-cfDNA, the D-OAR trial also reported a similar false positive rate of 91% when using the cutoff value of .2%. Allograft vasculopathy or any ischemic injury can raise the level of dd-cfDNA, 14 We acknowledge several limitations in our study. First, this is a single-center study with limited participants.…”
Section: Discussionmentioning
confidence: 96%
“…For dd-cfDNA, the D-OAR trial also reported a similar false positive rate of 91% when using the cutoff value of .2%. Allograft vasculopathy or any ischemic injury can raise the level of dd-cfDNA, 14 We acknowledge several limitations in our study. First, this is a single-center study with limited participants.…”
Section: Discussionmentioning
confidence: 96%
“…While these are “false-positive”, the increased levels of dd-cfDNA may be the result of other graft or endothelial injury that we are unable to detect in this study due to the limited follow-up time. 8 , 14 , 20 , 21 Other studies using combination of non-invasive surveillance methods in patients over 6 months post-transplant were able to avoid the need for EMBx in many more patient using combination dd-cfDNA and GEP testing than isolated GEP screening (83.9% vs. 72.2%) 22 .…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, a recent study noted an increase in dd-cfDNA in stable patients with cardiac allograft vasculopathy. 29 These findings expand the utility of dd-cfDNA beyond that of rejection and suggest potential future directions for its use.…”
Section: Cell-free Dnamentioning
confidence: 75%